Endoplasmic reticulum stress is induced in the human placenta during labour. Issue 1 (January 2015) - Veerbeek, J.H.W.; Tissot Van Patot, M.C.; Burton, G.J.; Yung, H.W.
Abstract: Placental endoplasmic reticulum (ER) stress has been postulated in the pathophysiology of pre-eclampsia (PE) and intrauterine growth restriction (IUGR), but its activation remains elusive. Oxidative stress induced by ischaemia/hypoxia-reoxygenation activates ER stress in vitro . Here, we explored whether exposure to labour represents an in vivo model for the study of acute placental ER stress. ER stress markers, GRP78, P-eIF2α and XBP-1, were significantly higher in laboured placentas than in Caesarean-delivered controls localised mainly in the syncytiotrophoblast. The similarities to changes observed in PE/IUGR placentas suggest exposure to labour can be used to investigate induction of ER stress in pathological placentas. Highlights: The process of labour activates endoplasmic reticulum stress response pathways in the human placenta. Labour may be used as an in vivo model to investigate molecular changes induced by endoplasmic reticulum stress. Downstream consequences of endoplasmic reticulum stress may compromise placental function in laboured samples ex vivo .